Identification and prioritization of factors affecting the saffron supply chain and selection strategies during the pandemic crisis based on the ANP-SWOT method - Farshid Riahi Dorcheh; Misagh Rahbari (Frontiers in Sustainable Food Systems)
PurposeIran is the world’s leading producer of saffron. This study aimed to investigate the challenges and provide some approaches to developing the supply chain of saffron, especially saffron exports during the coronavirus disease 2019 (COVID-19) pandemic.Design/methodology/approachIn this study, the strengths, weaknesses, opportunities, and threats (SWOT) of saffron exports were identified during the COVID-19 pandemic. Subsequently, the weights of the criteria, sub-criteria, and priorities of the presented strategies are computed using the AHP-SWOT and ANP-SWOT methods. Finally, data were acquired through the systematic collection of expert opinions using the Delphi method.FindingsAccording to the prioritization of saffron export development strategies during the COVID-19 pandemic based on the AHP-SWOT method, “Performing marketing research in universities” and “Creating international associations and using anti-COVID-19 tools” were identified as the most important strategies. Moreover, in the prioritization of saffron export development strategies during the COVID-19 pandemic based on the ANP-SWOT method, “Encouraging investors to attract investments and develop infrastructures” and “Performing marketing research in universities” are determined to be the most significant strategies.Originality/valueBecause of the COVID-19 pandemic, many economic problems have arisen for saffron-producing companies, highlighting the importance of implementing the best strategies to deal with these conditions. However, given the importance of saffron exports in Iran due to their high price and the occurrence of the COVID-19 pandemic crisis, it is imperative to conduct this research.